Paraburkholderia tropica as a plant-growth–promoting bacterium in barley: characterization of tissues colonization by culture-dependent and -independent techniques for use as an agronomic bioinput - García, Sabrina Soledad; Bernabeu, Pamela Romina; Vio, Santiago Adolfo; Cattelan, Natalia; Garcia, Julia Elena; Puente, Mariana Laura; María Lina, Galar; Prieto, Claudia Inés; Luna, María Flavia (Springer International Publishing, 2019)
Aims Characterization of barley-tissue–colonization efficiency (Hordeum vulgare L.) by Paraburkholderia tropica MTo-293 after seed inoculation was studied in two plant-growth systems: (1) in flasks with semisolid agar-containing sterile medium, as a suitable environment to study plant-bacteria interaction and also optimize molecular-biology techniques, and (2) in a potsubstrate system as an approach to understand their potential behavior as bioinput. Methods Culture-dependent techniques were implemented to quantify surface and endophytic bacterial populations in plant tissues. Culture-independent techniques were employed to detect and localize the inoculated bacteria in tissue samples along with evaluating the biofilm-forming capability by epifluorescent, confocallaser- scanning, and scanning-electron microscopy. Plant-growth parameters were measured to evaluate the effects of the inoculated acbteria on the development of the barley plants. Results Paraburkholderia tropica grew as a biofilm on both abiotic and biotic surfaces and efficiently colonized barley roots and stems in plants grown in flasks in presence of other microorganisms. The bacteria was localized on root surfaces, hairs, and central-cylinder areas. Paraburkholderia tropica also colonized the roots and stems in plants grown in the pot-substrate system. Although no endophytic root colonization occurred, the presence of the inoculated bacteria improved the aerial weight. A nested PCR detected P. tropica in the tissue samples. Conclusions Paraburkholderia tropica MTo-293 was characterized as an efficient biofilm-forming and barley- tissue–colonizing bacterium despite the presence of other microorganisms, but root endophytic colonization resulted dependent on the plant-growth system. Molecular-biology techniques were optimized, and also, its presence was correlated with plant-growth–promoting activity.